2022
DOI: 10.3390/su14074308
|View full text |Cite
|
Sign up to set email alerts
|

What Teachers Should Know for Effective Marine Litter Education: A Scoping Review

Abstract: Marine litter has had a huge impact on the marine environment and the socio-economic activities that depend on healthy oceans. All members of the community must play their part to address marine litter. Teachers are agents of change that are capable of encouraging pro-environmental practices among the community that will reduce environmental issues, including marine litter. However, teachers were found to have limited knowledge regarding ocean literacy and marine pollution. A scoping review was conducted to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Teachers have the ability to act as change agents and promote practices that address environmental issues, including the advancement of digital literacy, within the educational community [40]. However, some research has found that the knowledge of teachers about ocean literacy and marine pollution is restricted in the given field [40,41]. It is important to carry out educational projects that seek to integrate students, teachers, educational institutions, and the community to generate a virtuous circle around ocean literacy.…”
Section: Education and Ocean Literacymentioning
confidence: 99%
“…Teachers have the ability to act as change agents and promote practices that address environmental issues, including the advancement of digital literacy, within the educational community [40]. However, some research has found that the knowledge of teachers about ocean literacy and marine pollution is restricted in the given field [40,41]. It is important to carry out educational projects that seek to integrate students, teachers, educational institutions, and the community to generate a virtuous circle around ocean literacy.…”
Section: Education and Ocean Literacymentioning
confidence: 99%
“…This showed that BTC contribute to overcome marine environmental issues both through environtmental activities and programs even though they are not fully active. Education regarding marine litter is important to raise awareness in protecting the marine environment [64][65][66] which includes participation in overcoming the issues of MPL such as participating in sea and beach clean-up activities [38,40], campaigning for clean seas from plastic litter [41], as well as donations for marine environmental revitalization programs [42,43]. These results are also supported by the percentage of active participation category of BTC in overcoming the issues of MPL where as many as 15.69% of BTC had participation in the very good category, 56.86% of BTC had participation in the good category, 26.…”
Section: Participation Of Biology Teacher Candidas (Btc) To Overcome ...mentioning
confidence: 99%
“…Marine litter is a result of complicated waste management problems (Ahmad-Kamil et al, 2022) and it affects all the oceans of the Planet, from surface to seafloor, appearing in places as remote as the Artic or the Antarctica (Scotti et al, 2021;Parker, 2018). Parker (2018) used the map of Jason Treat drawing the distribution of marine plastic worldwide, the large accumulations of these materials, and the main rivers and land sources that transport these compounds to the sea.…”
Section: Introductionmentioning
confidence: 99%
“…Marine litter composition can be made of infinity materials, although plastic is the more visual material due to its floatability (Velis, 2014) and colors. Plastic litter has always been recorded to be the most abundant marine litter compared with other types of marine litter (Galgani et al, 2015;Aytan et al, 2020;Ahmad-Kamil et al, 2022). Plastics are important due to its daily use and functionality because it is the most versatile material of modern times (Plastics Europe, 2022).…”
Section: Introductionmentioning
confidence: 99%